Values Integration in Digital Pedagogy: A PRISMA-PICO Systematic Literature Review and Bibliometric Analysis - Subekhi, Khomad; Yahya, Yuniar Indra; Fauzi, Alim Achmad; Nursikin, Mukh (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examines values integration in digital pedagogy within open and distance learning by synthesizing conceptual and bibliometric evidence on the links among education, ethics, and socio-emotional development. A systematic literature review and bibliometric analysis were conducted using the PRISMA-PICO protocol. Four stages structured the synthesis: Identification (Population, 307 records), Screening (Intervention, 198 records), Eligibility (Comparison, 121 records), and Inclusion (Outcome, 117 records). VOSviewer was employed to map publication trends, country distribution, collaboration networks, and keyword co-occurrence. The results indicate prominent contributions from Indonesia and the United States, with more fragmented contributions from other regions. Diverse interventions were identified, including literacy-character models, hybrid outreach, systemic socio-emotional learning, and theological-cultural adaptation. Publication output increased during the global health emergency of the early 2020s, peaked in 2022, and was followed by stabilization and thematic diversification; the 2026 records are interpreted as partial-year coverage. Collaboration patterns suggest Indonesia's important role as a regional hub. Policy implications point to curriculum design, teacher capacity, and ethical use of technology as priorities for open and distance learning. The study is limited to Scopus-indexed articles in English, which may exclude relevant regional scholarship. By combining systematic review and bibliometric analysis under the PRISMA-PICO framework, this study offers substantive insights into values integration and a transparent methodological structure for bibliometric synthesis. The findings provide a conceptual basis for advancing inclusive, ethical, and resilient digital pedagogy.